Female Pelvic Vascular Malformations - Annam, Aparna (Seminars in Interventional Radiology, 2018)
Vascular malformations are classified primarily according to their flow characteristics, slow flow (lymphatic and venous) or fast flow (arteriovenous). They can occur anywhere in the body but have a unique presentation when affecting the female pelvis. With a detailed clinical history and the proper imaging studies, the correct diagnosis can be made and the best treatment can be initiated. Lymphatic and venous malformations are often treated with sclerotherapy while arteriovenous malformations usually require embolization. At times, surgical intervention of vascular malformations or medical management of lymphatic malformations has been implemented in a multidisciplinary approach to patient care. This review presents an overview of vascular malformations of the female pelvis, their clinical course, diagnostic studies, and treatment options.
Keywords: interventional radiology; vascular malformation; sclerotherapy; venous malformation; lymphatic malformation; arteriovenous malformation